Reflective Teacher Supervision Through Videos of Classroom Teaching - Sandra Mari Kaneko-Marques (Universidad Nacional de Colombia, 2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.